The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1590/s0100-879x2001000800013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exercise on the activity and the distribution between free and bound forms of glycolytic and associated enzymes in tissues of horse mackerel

Abstract: The effects of short-term burst (5 min at 1.8 m/s) swimming and longterm cruiser (60 min at 1.2 m/s) swimming on maximal enzyme activities and enzyme distribution between free and bound states were assessed for nine glycolytic and associated enzymes in tissues of horse mackerel, Trachurus mediterraneus ponticus. The effects of exercise were greatest in white muscle. The activities of phosphofructokinase (PFK), pyruvate kinase (PK), fructose-1,6-bisphosphatase (FBPase), and phosphoglucomutase (PGM) all decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
(37 reference statements)
2
13
0
Order By: Relevance
“…During exercise one expects an increased production and accumulation of lactate due to the need of degrading rapidly glucose to obtain energy for the muscle (11,12,26,35). In our study this finding was observed in liver tissue of the nontreated group but not in the muscle.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…During exercise one expects an increased production and accumulation of lactate due to the need of degrading rapidly glucose to obtain energy for the muscle (11,12,26,35). In our study this finding was observed in liver tissue of the nontreated group but not in the muscle.…”
Section: Discussionsupporting
confidence: 43%
“…It has been reported alterations in enzyme activities and binding interactions in fish brain, liver and muscle during exercise. These alterations are dependent on exercise intensity (26).…”
mentioning
confidence: 99%
“…LDH activity assay LDH activity was surveyed by following the study of Lushchak et al (2001), assayed by monitoring the change in NADH absorbance at 340 nm. One unit of enzyme activity was defined as the amount of enzyme consuming 1 μmol of substrate per minute.…”
Section: Cat Activity Assaymentioning
confidence: 99%
“…Its activity has been found and characterized in many fish species and tissues, such as liver, skeletal and cardiac muscles, brain and gills from rainbow trout, horse mackerel, gilthead sea bream and carp [3,6,[29][30][31][32][33][34]. In these studies, HK is generally used as a model for changes induced by a wide range of stresses, such as hypoxia, exercise, carbohydrate tolerance and temperature.…”
Section: Introductionmentioning
confidence: 99%